Comparison of Treatment Efficacy and Survival Outcomes Between Asian and Western Patients With Unresectable Gastric or Gastro-Esophageal Adenocarcinoma: A Systematic Review and Meta-Analysis - Zhang, Zhening; Liu, Zining; Chen, Zeyang (Frontiers in Oncology, 2022)
Background: Gastric cancer and gastro-esophageal adenocarcinoma are geographically heterogeneous diseases. Previous studies suggested that Asian and Western patients with late-stage gastric or gastro-esophageal adenocarcinoma possess distinct survival outcomes. However, the interregional differences of multiple systemic therapies in unresectable diseases have not been comprehensively described. Materials and methods: We searched PubMed-MEDLINE, Embase, Web of Science and Cochrane Library from inception to 31 October 2021 and reviewed major conference abstracts for controlled trials of systemic therapies in unresectable gastric or gastro-esophageal adenocarcinoma that reported hazard ratios stratified by geographical region. The primary measurements were overall survival and progression-free survival. The pooled hazard ratios and 95% confidence intervals for overall survival and progression-free survival in Asian and Western populations were calculated using a random effect model. A linear regression model was adopted to compare the overall survival and progression-free survival between Asian and Western patients. Results: A total of 9033 patients from 20 studies were included for analysis. Immunotherapy was associated with an improvement in the overall survival for both Asian (hazard ratio, 0.80; 95% confidence interval, 0.65–0.98) and Western (hazard ratio, 0.90; 95% confidence interval, 0.81–1.00) patients, with no significant difference between the two groups (P = 0.32). Trends of survival benefit with anti-HER2 therapy and anti-angiogenic therapy versus control were observed in both Asian and Western patients, although statistical significance was not denoted. Subgroup analyses yielded a statistically superior overall survival of Asian versus Western patients in trials that investigated first-line immunotherapy (P = 0.04). Due to the linear regression analyses with scatter plot graphs, Asian patients showed a higher overall survival, but not progression-free survival, than Western patients irrespective of treatment type. Conclusion: Asian and Western patients with unresectable gastric or gastro-esophageal adenocarcinoma show similar responses to systemic therapies with limited interregional differences. Exceptionally, first-line immunotherapy could elicit superior survival among Asian populations. In addition, Asian patients with gastric or gastro-esophageal adenocarcinoma display a superior OS compared with Western counterparts.